Pengembangan Modul Tematik Terintegrasi Al-Qur’an dan Hadis Pada Tema Cuaca di Kelas III Sekolah Dasar - uswatun hasanah yusid; Eka Filahanasari; Moh Rosyid Mahmudi (SCHOLASTICA JOURNAL JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2022)
This research is motivated by learning that only focuses on the teacher's book, so that the teacher gives very little understanding of Islamic values to students and teachers find it difficult to instill character values in students. The material in thematic textbooks and modules is not yet available which is integrated with the Qur'an and Hadith. Even though learning resources that are integrated with the Qur'an and Hadith are needed at the elementary school in accordance with the school's vision, namely loving knowledge, sincere in charity, ready to preach and patiently living it. So that teaching materials are needed that link the Qur'an and Hadith as an effort to overcome these problems, namely the need for efforts to develop teaching materials for the Integrated Thematic Module of the Qur'an and Hadith on the Weather Theme in grade III Elementary School.This type of research is a Research and Development (R&D) research by prioritizing the ADDIE development model which consists of several stages (Analyze, Design, Development, Implimantation, Evaluation). The test subjects are third grade students of SD IP Daaruth Thullab 02 Koto Salak. The data collection instrument used an assessment instrument in the form of a validation sheet, the practicality and effectiveness of this assessment instrument were validated by three validators, content balladators, language validators, and construct validators.The use of teaching materials for the Integrated Thematic Module of the Qur'an and Hadith on the Weather Theme in grade III Elementary School. The results of the module validation carried out by 3 validators obtained an average validity value of 78.95% in the valid category, the practicality value obtained a value of 93% in the very practical category. And the value of effectiveness obtained a value of 66,68%. It can be concluded that the Thematic Integrated Module of the Qur'an and Hadith on the Weather Theme in grade III Elementary School is valid and can be used by teachers and students.